2009
DOI: 10.5205/reuol.202-1995-3-ce.0302200913
|View full text |Cite
|
Sign up to set email alerts
|

Diagnósticos de enfermagem em gestantes atendidas em Unidade de Saúde da Família

Abstract: Objective: to elaborate the profile of nursing diagnoses in pregnant women assisted in a Family’s Health Unit based on NANDA-I’s Taxonomy II. Method: this is about a retrospective study, analytic descriptive, regards to analysis from 20 pregnant women handbooks registered in the prenatal program from a family’s health unit. Data were collected in July 2008, with a form composed of three parts: partner-demographic data, obstetric data and referring data to defining characteristics and related factors (of risk) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…Establishing causal relationship and evidence for practice Leite et al (2009) identified EFV in 12,5% of low risk pregnant women in a primary health care center, having compromised regulatory mechanisms as causal factor evidenced by edema in lower limbs. The term compromised regulatory mechanisms refers to the imbalance in the maintenance of body fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing causal relationship and evidence for practice Leite et al (2009) identified EFV in 12,5% of low risk pregnant women in a primary health care center, having compromised regulatory mechanisms as causal factor evidenced by edema in lower limbs. The term compromised regulatory mechanisms refers to the imbalance in the maintenance of body fluids.…”
Section: Discussionmentioning
confidence: 99%
“…O checklist do estudo presente foi idealizado de modo a considerar que as mulheres apresentam algumas demandas relacionadas a sua condição gestacional. Alguns dos diagnósticos evidenciados no instrumento também foram apontados em outros estudos 8,9 como o conhecimento sobre saúde, náusea, dor, comportamento alimentar e obstipação. Embora, ambos tenham utilizados a Taxonomia II da NANDA-I como base de classificação.…”
Section: Discussionunclassified